Immunotherapeutic allogeneic dendritic cell and autologous tumor cell fusion vaccine alone or combined with radiotherapy in canine oral malignant melanoma is safe and potentially effective - Xia, Yuan-Yuan; Liao, Albert TaiChing; Liu, Ru-Min; Yang, Shu-Ya; Kuo, Chien-Chun; Ke, Chiao-Hsu; Lin, Chen-Si; Lee, Jih-Jong (Frontiers in Veterinary Science, 2024)
Introduction: Immunotherapy represents a promising breakthrough in cancer management and is being explored in canine melanomas. Dendritic cells (DCs) play a crucial role in priming T-cell mediated immune reactions through the antigen-presenting function. Combining immunotherapy and radiation therapy may generate more substantial anti-cancer efficacy through immunomodulation. Objectives: Our research reported a preliminary result of the safety and outcome of a kind of immunotherapy, the allogeneic dendritic cell and autologous tumor cell fusion vaccine, alone or in combination with hypofractionated radiation therapy, in canine oral malignant melanoma. Methods: Two groups of dogs with histopathological diagnoses of oral malignant melanoma were recruited. In group 1 (DCRT), dogs received a combination of DC fusion vaccine and radiotherapy. In group 2 (DC), dogs received DC fusion vaccine alone. DC vaccination was given once every two weeks for four doses. Radiotherapy was performed weekly for five fractions. Dogs that received carboplatin were retrospectively collected as a control group (group 3). Results: Five dogs were included in group 1 (two stage II, three stage III), eleven in group 2 (three stage I/II, eight stage III/IV), and eight (two stage I/II, six stage III/IV) in the control group. Both DC and DCRT were well-tolerated, with only mild adverse events reported, including mucositis, gastrointestinal discomfort and injection site reactions. The median progression-free intervals in groups 1, 2 and 3 were 214 (95% CI, NA, due to insufficient data), 100 (95% CI, 27-237), and 42 days (95% CI, NA-170), respectively, which were not significantly different. The 1-year survival rates were 20%, 54.5%, and 12.5% in groups 1, 2 and 3. Dogs in the DCRT group exhibited significantly higher TGF-β signals than the DC group throughout the treatment course, indicating a possible higher degree of immunosuppression. Conclusion: The manuscript demonstrated the safety of dendritic cell/tumor cell fusion vaccine immunotherapy, alone or in combination with radiotherapy. The results support further expansion of this immunotherapy, modification of combination treatment and protocols, and investigation of combining DC vaccine with other treatment modalities.